STUDI LITERATUR PENGARUH TERAPI NEBILISER PADA PASIEN ASMA - Azizah, Siti; Sasono, Tri Nurhudi (Universitas Harapan Bangsa Purwokerto, 2020)
Asthma is a health problem that is still commonly found in the environment around us, with prominent symptoms are measa shortness of breath, and an increase in the frequency of breathing, resulting in breathing patterns become ineffective. . One intervention that is usually given by a doctor in a hospital is the administration of a nebulizer, which can relieve asthma symptoms. The purpose of writing this literature is to conduct a literature review analysis of Nebulizer administration in bronchial as Asthma is a health problem that is still commonly found in the environment around us, with prominent symptoms are measa shortness of breath, and an increase in the frequency of breathing, resulting in breathing patterns become ineffective. . One intervention that is usually given by a doctor in a hospital is the administration of a nebulizer, which can relieve asthma symptoms. The purpose of writing this literature is to conduct a literature review analysis of Nebulizer administration in bronchial asthma. namely through national and international articles obtained from google scholar and crossref, the articles used were articles published in 2010-2020 with a total of 6 articles that fit the inclusion criteria. Data obtained, analyzed and compiled systematically and discussed. The results showed that the administration of nebulizer in bronchial asthma was very influential and efficient in relieving bronchial asthma, either by dilution or without dilution. thma. namely through national and international articles obtained from google scholar and crossref, the articles used were articles published in 2010-2020 with a total of 6 articles that fit the inclusion criteria. Data obtained, analyzed and compiled systematically and discussed. The results showed that the administration of nebulizer in bronchial asthma was very influential and efficient in relieving bronchial asthma, either by dilution or without dilution.